(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The use of self-healing concrete reduces the need for costly maintenance and repairs. However, research on the durability of self-healing concrete remains limited. The latest research demonstrates the ability of self-healing concrete to withstand chloride incursions. Electron probe microanalysis and chloride profiles demonstrated the effectiveness of the technique in self-healing concrete with macro-encapsulated polyurethane, reducing chloride penetration into cracks and from the fracture into the concrete matrix. Additionally, we investigated the corrosion behavior of specimens of reinforced concrete when exposed to a NaCl solution on a cyclic basis. Autonomous crack healing has the potential to drastically lower corrosion during the propagation stage, according to the electrochemical studies. The rebars showed no visible damage after 44 weeks of exposure. Conversely,fractured samples lacking an integrated self-healing mechanism had active corrosion after ten weeks of exposure, and after twenty-six weeks, rebars showed obvious pitting damage. Bacteria-based treatments require several weeks to cure a 300 µm fissure, but encapsulated polyurethane allows for self-healing in an hour. During the crack healing process, bacterial granules containing denitrifying cultures produced nitrite, an intermediate metabolic product, which shielded the reinforcement.